The lost jewels [large type] - Manning, Kirsty (Thorndike Press, a part of Gale, a Cengage Company, 2021)
An American jewelry historian discovers her unexpected ties to a fortune in jewels discovered under the floor of a London tenement house where an impoverished Irish immigrant once attempted to change her family's fortunes.